N-Glycan Modifications with Negative Charge in a Natural Polymer Mucin from Bovine Submaxillary Glands, and Their Structural Role - Kim, Jihye (Polymers (Basel), 2020)
Bovine submaxillary mucin (BSM) is a natural polymer used in biomaterial applications for its viscoelasticity, lubricity, biocompatibility, and biodegradability. N-glycans are important for mucin stability and function, but their structures have not been fully characterized, unlike that of O-glycans. In this study, BSM N-glycans were investigated using liquid chromatography-tandem mass spectrometry. The microheterogeneous structures of 32 N-glycans were identified, and the quantities (%) of each N-glycan relative to total N-glycans (100%) were obtained. The terminal N-acetylgalactosamines in 12 N-glycans (sum of relative quantities; 27.9%) were modified with mono- (10 glycans) and disulfations (2 glycans). Total concentration of all sulfated N-glycans was 6.1 pmol in BSM (20 µg), corresponding to 25.3% of all negatively charged glycans (sum of present N-glycans and reported O-glycans). No N-glycans with sialylated or phosphorylated forms were identified, and sulfate modification ions were the only negative charges in BSM N-glycans. Mucin structures, including sulfated N-glycans located in the hydrophobic terminal regions, were indicated. This is the first study to identify the structures and quantities of 12 sulfated N-glycans in natural mucins. These sulfations play important structural roles in hydration, viscoelasticity control, protection from bacterial sialidases, and polymer stabilization to support the functionality of BSM via electrostatic interactions.